Opening digital fabrication: transforming TechKnowledgies - Schneider, Christoph (KIT Scientific Publishing, 2018)
This study analyses the field of open digital fabrication where novel digital capabilities and hopes for social transformation have merged to form arrangements that seek to democratise knowledge and technology through collaboration. Through qualitative social science the study analyses FabLabs and open source technologies and the respective collective procedures that produce and organise technology and knowledge that redefine the entanglement of our society and its technologies.